Employee’s work on the grounds of Polish Copyright Law - Szymura, Monika (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Employees’ works are crucial in practice. The validity and need for discussions on the rights of the employer to the employee’s work is justified by the increasing concern for the observance of copyright, and also for employee–employer relations. By entering into an employment relationship, both parties must be aware of their rights and obligations. Aim: This article presents the issue of copyright status of an employee’s work regulated in the Article 12 and 13 of the Act on copyright and related rights. The considerations focus on the legal relationship between the employer and the employee-author, and the issue of acquiring author’s economic rights to the work created by the employee within the employment relationship. The article is based on the analysis of legal regulations and judicial decisions. Results: Regulating rights to the work created by the employee is dependent on the will of the parties. It is only the absence of contractual terms in this respect that results in a reference to the statutory provisions, which define the rules of transferring copyright for the employee’s work to the employer. Article 12 of the Act on copyright and related rights specifies grounds for secondary acquisition of copyright by the employer. One should remember that this regulation concerns solely author’s economic rights because author’s moral rights, which due to their nature are non-transferable, remain with the author or employee.